Den oldengelske digtning og Grundtvig - Noack, Bent (Grundtvig-studier, 1989)
Grundtvig and Anglo-Saxon Poetry By Bent Noack. Grundtvig’s work on Anglo-Saxon poetry and his use of it is, in many respects, an important part of his legacy to his people and his church. It was the historian Grundtvig who, at the beginning of his career, used the Beowulf Poem in his mythological studies and both welcomed and criticized Thorkelin’s 1815 edition of it. His work on Beowulf went on, almost till the end of his life, with translations, reproduction and, finally, an edition in 1861.His journeys to England in 1829 to 1831 also had historical and mythological studies as their main purpose. But soon Grundtvig became aware that England possessed an important group of manuscripts of biblical and religious poetry, the Exeter Book being the most outstanding. He planned an edition, in England, of ’the most valuable Anglo-Saxon manuscripts’, as he said in his ’prospectus’ for a subscription. Part of the plan was eventually carried out by Benjamin Thorpe, but Grundtvig’s work was not done for nothing: many of his readings and emendations are still maintained. In 1840, he published an edition of the ’ Phoenix’ with introduction and translation.As a hymn writer Grundtvig reproduced pieces of Anglo-Saxon poetry; his collected hymns contain eight reproductions, and two of them are still among the most cherished of his hymns.